Afoxolaner as a Treatment for a Novel Sarcoptes scabiei Infestation in a Juvenile Potbelly Pig - Smith, Joe S.; Berger, Darren J.; Hoff, Sarah E.; Jesudoss Chelladurai, Jeba R. J.; Martin, Katy A.; Brewer, Matthew T. (Frontiers in Veterinary Science, 2020)
A 2 month old female Vietnamese pot bellied pig presented to a veterinary teaching hospital with a referring complaint of pruritus. A human caretaker of the pig had recently been diagnosed with a Sarcoptes spp. dermatitis. Microscopic examination of the skin scrape samples and BLAST analysis confirmed the species of the mite as most closely related to Sarcoptes scabiei var. canis (AY493391). The pig was treated with afoxolaner as previous treatment with ivermectin was not efficacious. Recheck examinations and follow up revealed the pig to be non-pruritic and resolving. Afoxolaner may be a therapeutic option when treating Sarcoptes spp. infections in companion pigs.